Exploring the needs of TPACK-based learning activity types website analysis for the seventh graders - Pratiwi Amelia; Rindu Handayani (Universitas Muhammadiyah Malang, 2026)
This study investigates the requirements of seventh-grade students and English teachers in Bangka Belitung for a TPACK-based Learning Activity Types (LATs) website to enhance English language acquisition. The research utilised a concurrent triangulation mixed-methods approach to reconcile student learning preferences with available instructional materials. Data were gathered from 99 seventh-grade students using a needs analysis questionnaire and from four English teachers through semi-structured interviews at SMP Negeri 5 Pangkalpinang. Quantitative data demonstrate that whereas students exhibit robust basic communication abilities (93% accuracy in welcomes), substantial deficiencies are seen in morphosyntax and tense construction (55% accuracy). Students demonstrated a strong inclination for interactive, audiovisual learning (92%) on subjects including Family (85%) and Environment (82%). Qualitative findings from teacher interviews indicate a